A comparative techno-economic assessment of CO2 mineralization technologies: A case study from the construction sector - Ali Abdelshafy; Till Strunge; Dietmar Stephan; Grit Walther (Journal of CO2 Utilization)
CO2 mineralization is a crucial carbon capture and utlization technique because it can sequester CO2 emissions permanently. There are various CO2 mineralization technological pathways, all of which are based on the reaction of CO2 with the metal oxides present in cementitious materials and virgin minerals. However, there are techno-economic obstacles that hinder their deployment, as well as various knowledge gaps regarding the prospective supply chains. Although these pathways have several differences, such as process configuration and costs, each is usually addressed individually and comparative analysis is lacking. In this contribution, we aim to address this knowledge gap via investigating the entire supply chain of each technology and contrasting their differences by presenting a case study from the German federal state of North Rhine-Westphalia. Methodologically, several approaches and tools are used, such as cost modeling and geographic information systems. Herein, we investigate the advantages and limitations by assessing six scenarios representing the different configurations of the relevant supply chains. Most scenarios are deemed infeasible at lower carbon prices, with only three considered viable below 100 €/ton CO2. Also, while concrete curing and concrete waste processes are constrained by material availability and logistics, CO2 mineralization of virgin minerals offers a more abundant alternative, albeit at a higher levelized cost. Therefore, the study provides valuable insights for the design of optimal and efficient CO2 mineralization supply chains, highlighting the need for a balanced approach that leverages the strengths of different pathways.